Metal oxide nanoparticles interact with immune cells and activate different cellular responses - Simón-Vázquez R (Dove Medical Press, 2016)
Rosana Simón-Vázquez, Tamara Lozano-Fernández, Angela Dávila-Grana, Africa González-Fernández Immunology Laboratory, Biomedical Research Center (CINBIO) and Institute of Biomedical Research of Ourense-Pontevedra-Vigo (IBI), University of Vigo, Campus Lagoas Marcosende, Vigo, Pontevedra, Spain Abstract: Besides cell death, nanoparticles (Nps) can induce other cellular responses such as inflammation. The potential immune response mediated by the exposure of human lymphoid cells to metal oxide Nps (moNps) was characterized using four different moNps (CeO2, TiO2, Al2O3, and ZnO) to study the three most relevant mitogen-activated protein kinase subfamilies and the nuclear factor kappa-light-chain-enhancer of the activated B-cell inhibitor, IκBα, as well as the expression of several genes by immune cells incubated with these Nps. The moNps activated different signaling pathways and altered the gene expression in human lymphocyte cells. The ZnO Nps were the most active and the release of Zn2+ ions was the main mechanism of toxicity. CeO2 Nps induced the smallest changes in gene expression and in the IκBα protein. The effects of the particles were strongly dependent on the type and concentration of the Nps and on the cell activation status prior to Np exposure. Keywords: Jurkat, MAPK, NFκB, qPCR, inflammation, metabolism